UMP, Germany's Mannheim University to offer chemical engineering dual degree programme - T.N., Alagesh (New Straits Times, 2023)
PEKAN: Universiti Malaysia Pahang (UMP) has signed a second cooperation agreement with Germany's Mannheim University of Applied Sciences (HMA), following a successful collaboration in the business engineering programme last year.